Development Of Asarone-free Piper Sarmentosum Roxb. Extracts Using Supercritical Carbon Dioxide Pre-treatment And Studies On Their Stability, Cytotoxicity And Enzyme Inhibition - Hamil, Mohd Shahrul Ridzuan (2023)
Piper sarmentosum Roxburgh is a herbaceous shrub with numerous pharmacological benefits. However, the presence of two toxic phenylpropanoids (α- and β-asarone) has limited the usage of the plant for medicinal purposes. The objectives of the present study include phytochemical analysis of supercritical carbon dioxide (SC-CO2) extract, optimization of SC-CO2 for maximum removal of α-, β- and ɣ-asarone, comparative study between SC-CO2 pre-treated and untreated P. sarmentosum leaf extracts to evaluate their metabolites profiles, bioactivities and stability. The leaves of P. sarmentosum were extracted using SC-CO2 and conventional solvent maceration method to compare the efficiency of asarone extraction. Optimization of asarone extraction was conducted using the Box-Behnken experimental design. SC-CO2 residue was re-extracted using ethanol, 50% ethanol and water, and their chemical and biological profiles were compared with those of leaf material without SC-CO2 pre-treatment. SC-CO2 extraction selectively extracted α-, β- and ɣ-asarone with more than two folds compared to conventional solvent extraction method. Gas chromatography-mass spectrometry (GC-MS) analysis of SC-CO2 extract identified α-asarone (28.18%) as the major component in the extract, followed by γ-asarone (25.70%), phytol (9.66%), asaricin (11.20%) and vitamin E (4.85%). Optimized SC-CO2 condition to maximize the extraction of α-, β- and ɣ-asarone was obtained at pressure = 81.16 bar, temperature = 50.11°C and extraction time = 80.90 min. High performance liquid chromatography (HPLC) analysis of the optimized method showed 13.91% α-asarone, 3.43% β-asarone and 14.95% ɣ-asarone, respectively. SC-CO2 residue of the leaves re-extracted with conventional solvents showed a significant decrease of asarone ranging from 45 to 100% (p<0.001) as compared to their counterpart without SC-CO2 treatment. α-, β- and ɣ-asarone were completely removed in the ethanol and 50% ethanol extracts of the residue, whereas the isomers were absent in water extract.